Master Class with William Christie and Paul Agnew On the Ruckers/Taskin harpsichord (1646) - Leclair, Jean-Marie 1697-1764; Handel, George Frideric 1685-1759; Leclair, Jean-Marie 1697-1764; Handel, George Frideric 1685-1759 (Les Arts Florissants, 2019)
In addition to helming the celebrated Arts Florissants ensemble, William Christie and Paul Agnew are both accomplished pedagogues. In this master class at the Philharmonie de Paris, the pair work with students from the Juilliard School and the Paris Conservatory on a historic instrument that is one of the crowning jewels of the Museum of Music's collection: the Ruckers/Taskin harpsichord dating from 1646. Photo: Paul Agnew and William Christie © Oscar Ortega
Keywords: masterclass; Songs; Sonatas; Overtures; Filmed performances; Dramatic music; Chamber music; Internet videos